2021
DOI: 10.1002/agt2.124
|View full text |Cite
|
Sign up to set email alerts
|

Mesogens with aggregation‐induced emission properties: Materials with a bright future

Abstract: Within the past two decades, chromophores, which show aggregation-induced emission (AIE), have gained considerable attention with respect to the development of luminescent liquid crystals. In contrast to common luminogens, AIE emitters do not suffer from aggregation-caused quenching of the emission in the solid state. In this review, we summarize the recent development in the field of AIE-active liquid crystals and show first model devices, which already prove the application potential of these materials. Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 93 publications
0
30
0
Order By: Relevance
“…Next, we employed imine exchange to introduce additional properties into the liquid crystalline materialnamely fluorescence. As the fluorescence strongly depends on the molecular surrounding and packing of the luminophore, materials combining the liquid crystalline behavior with fluorescence have gained considerable attention with respect to the development of thermoresponsive functional materials. Here, we employed the hydroxyl benzaldehyde derivative Ald-3 in an imine exchange reaction with imine Im-4f (Figure ) to induce fluorescence. Upon one heating/cooling cycle, a significant decrease of the clearing point and melting temperature was observed in comparison to the initial Im-4f (from 92 to 60 °C and 88 to 39 °C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Next, we employed imine exchange to introduce additional properties into the liquid crystalline materialnamely fluorescence. As the fluorescence strongly depends on the molecular surrounding and packing of the luminophore, materials combining the liquid crystalline behavior with fluorescence have gained considerable attention with respect to the development of thermoresponsive functional materials. Here, we employed the hydroxyl benzaldehyde derivative Ald-3 in an imine exchange reaction with imine Im-4f (Figure ) to induce fluorescence. Upon one heating/cooling cycle, a significant decrease of the clearing point and melting temperature was observed in comparison to the initial Im-4f (from 92 to 60 °C and 88 to 39 °C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…As mentioned earlier, the design of fluorescent liquid crystalline materials is an interesting research subject for the numerous potential applications they offer in various fields (in optical sensing and detection, as probes, or optoelectronic displays). 57 S -Containing hetero-aromatics usually have outstanding optical properties. The photophysical properties of these new compounds were studied by UV-vis absorption in solution and fluorescence emission in both solution and thin film states (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregation‐caused quenching (ACQ) effect, which refers to the phenomenon that highly emissive fluorophores become weakly emissive or non‐emissive upon aggregation by π–π stacking due to the formation of nonradiative charge‐transfer complexes, may reduce background fluorescence to some extent. [ 43–45 ] However, the ACQ effect is generally not absolute for most conventional probes, owing to which fluctuated background fluorescence exists and causes certain interference when applied to the determination of CMC. Previously, we reported a series of near‐infrared aza ‐BODIPY fluorescence probes for accurate in vivo tracing of various nanocarriers and found that the fluorescence of these probes could be quickly and absolutely quenched.…”
Section: Introductionmentioning
confidence: 99%